Influence of fine materials on stress-strain and degradation behavior of railway ballast under static loading conditions. - Navaratnarajah, S.K.; Venuja, S.; Shahmi, N.M.; Rimas, N.M. (Graduate Associate Professionals (Pvt) Ltd, 2019)
Ballast is a selected, crushed, granular material used for supporting train load through sleepers and rail in a rail track foundation system. It is used highly because of the availability of low-cost raw materials and has many technical advantages such as free drainage and high lateral resistance among others. But fast and heavy haul train loads and with many external environmental factors foul the ballast material and change its load deformation and degradation behavior. Ballast fouling from the intrusion of foreign materials such as water-driven and wind- flown fine soil particles (predominately silt or very fine sand and clay) or mud pumping from underneath the subgrade layer is inevitable. These processes continuously contaminate the ballast particles and change their physical and mechanical property which leads to a change in shear strength and stability of the ballast layer. This study mainly focuses on the influence of different types of fine materials intrusion on shear and degradation behavior of railway ballast used in Sri Lankan rail tracks. Clay and fine sand were used as fouling materials in this study. A series of large scale direct shear testing was performed considering full-size ballast particles with and without ballast fouling for different loads. The findings show that when the sand fouling percentage increases, the shear strength tends to increase due to the increase of density of the material. When the ballast contaminated with clay material, the shear strength of the fouled ballast tends to decrease. Ballast breakage analysis shows that the breakage increasing with higher vertical stress, but decreasing with ballast fouling.
Keywords: Ballast; Sleepers; Fouling; Degradation; Fine materials